2021
DOI: 10.1021/acs.analchem.0c04191
|View full text |Cite
|
Sign up to set email alerts
|

Allele-Specific Recombinase Polymerase Amplification to Detect Sickle Cell Disease in Low-Resource Settings

Abstract: Sickle cell disease (SCD) is a group of common, life-threatening disorders caused by a point mutation in the β globin gene. Early diagnosis through newborn and early childhood screening, parental education, and preventive treatments are known to reduce mortality. However, the cost and complexity of conventional diagnostic methods limit the feasibility of early diagnosis for SCD in resource-limited areas worldwide. Although several point-of-care tests are commercially available, most are antibody-based tests, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Hence, the authors suggested further confirmatory validation. Another study by Natoli et al reported a strategy for allele-specific detection of the sickle cell mutation using blood samples [ 18 ]. In their assay, two separate reactions for each sample are required to detect AA and SS genotypes, which is the major limitation of the above study.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the authors suggested further confirmatory validation. Another study by Natoli et al reported a strategy for allele-specific detection of the sickle cell mutation using blood samples [ 18 ]. In their assay, two separate reactions for each sample are required to detect AA and SS genotypes, which is the major limitation of the above study.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Natoli et al have reported a strategy for allele-specific detection of sickle cell mutation using blood samples. 18 In their assay, two separate reactions for each sample are required to detect AA and SS genotypes, which is the major limitation of the above study.…”
Section: Discussionmentioning
confidence: 99%
“…For the detection of single-point mutations, some RPA-based approaches have been described, such as RPA-microarray hybridization, 8 real-time RPA, 9 and zip-RPA. 10 A relevant variant, called blocked-RPA, was developed for selective amplification of particular DNA variants based on the enrichment of minority alleles.…”
Section: Introductionmentioning
confidence: 99%